Bacterial Culture Streak Method for Inventory of Enterobacteriaceae Causes Diarrhea in the Body of House Fly (Musca Domestica) - Urip Urip; Titin Emilia Nirmala Sari; Maruni Wiwin Diarti; Erlin Yustin Tatontos (Jurnal Penelitian Pendidikan IPA, 2023)
Diarrhea is an endemic disease in Indonesia and is a potential disease Extraordinary Events (KLB) which are often accompanied by death. Based on data on diarrhea cases at the Narmada Community Health Center in 2017 there were 1.679 cases of diarrhea from 11 villages in Narmada District. One of the causes of these cases of diarrhea is the presence of house flies as a vector carrying disease. The purpose of this study was to determine the bacterial culture of the streak method for inventory of Enterobacteriaceae of diarrhea in the body of the house fly (Musca domestica). This research is descriptive observational. The sample in this study were 30 Musca domestica which were captured in the Kramajaya village environment in Nutrienth Agar Plate (NAP) and Mac Conkey Agar (MCA) media as well as the INVIC MUTSI Biochemical Test media on bacterial colonies that needed further identification to determine species. The analysis of the results was carried out descriptively. The identification results were found in the family Enterobacteriaceae genus Enterobacter agglomerans in the body of the house fly (Musca domestica) samples taken from the landfill and the family Moraxellaceae family genus Acinetobacter baumannii taken from the kitchen and home terrace